Angiogenic conditioning of peripheral blood mononuclear cells promotes fracture healing. Issue 8 (August 2017) - Mifuji, K.; Ishikawa, M.; Kamei, N.; Tanaka, R.; Arita, K.; Mizuno, H.; Asahara, T.; Adachi, N.; Ochi, M.
Abstract : Objectives: The objective of this study was to investigate the therapeutic effect of peripheral blood mononuclear cells (PBMNCs) treated with quality and quantity control culture (QQ-culture) to expand and fortify angiogenic cells on the acceleration of fracture healing. Methods: Human PBMNCs were cultured for seven days with the QQ-culture method using a serum-free medium containing five specific cytokines and growth factors. The QQ-cultured PBMNCs (QQMNCs) obtained were counted and characterised by flow cytometry and real-time polymerase chain reaction (RT-PCR). Angiogenic and osteo-inductive potentials were evaluated using tube formation assays and co-culture with mesenchymal stem cells with osteo-inductive medium in vitro . In order to evaluate the therapeutic potential of QQMNCs, cells were transplanted into an immunodeficient rat femur nonunion model. The rats were randomised into three groups: control; PBMNCs; and QQMNCs. The fracture healing was evaluated radiographically and histologically. Results: The total number of PBMNCs was decreased after QQ-culture, however, the number of CD34+ and CD206+ cells were found to have increased as assessed by flow cytometry analysis. In addition, gene expression of angiogenic factors was upregulated in QQMNCs. In the animal model, the rate of bone union was higher in the QQMNC group than in the other groups. Radiographic scores and bone volume were significantly associated with the enhancement of angiogenesis in the QQMNC group. Conclusion: We have demonstrated that QQMNCs have superior potential to accelerate fracture healing compared with PBMNCs. The QQMNCs could be a promising option for fracture nonunion. Cite this article : K. Mifuji, M. Ishikawa, N. Kamei, R. Tanaka, K. Arita, H. Mizuno, T. Asahara, N. Adachi, M. Ochi. Angiogenic conditioning of peripheral blood mononuclear cells promotes fracture healing. Bone Joint Res 2017;6: 489–498. DOI: 10.1302/2046-3758.68.BJR-2016-0338.R1.